Opsoclonus-myoclonus syndrome following long-term use of cyclosporine. (4th May 2018) - Kang, Hyun Goo; Park, Sung Kwang; Wang, Su Jeong; Oh, Sun-Young; Ryu, Han Uk
Abstract: Background: Cyclosporine A (CsA) is a widely used immunosuppressive agent that may provoke unexpected neurologic complications. The mechanism is unclear and variable intervals have been reported between CsA administration and onset of the related side effects. Here, we describe a case of delayed-onset CsA neurotoxicity presenting as opsoclonus-myoclonus syndrome (OMS). Case details: A 37-year-old woman with a two-week period of opsoclonus and upper extremity myoclonus was admitted to our hospital. The patient had been taking CsA for 17 years after receiving a kidney transplant. Further evaluation did not reveal any other abnormalities. Seven days after switching from CsA to tacrolimus, in the absence of additional immune-modulating therapy, her neurologic symptoms improved considerably. Conclusion: This is the case of delayed, long-term complications of CsA presenting as OMS. Symptoms resolved by substituting CsA with another immunomodulating drug. The etiology of the neurologic complications may involve paradoxically-enhanced delayed-type hypersensitivity.